China's Imports Slowdown : Spillovers, Spillins, and Spillbacks - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2016)
The paper models international spillovers from a hypothetical drop of China's imports as a result of China's rebalancing of its growth model. A network-based model used in the paper allows capturing higher round network effects of the shock, which are largely unaccounted for in the existing literature. Such effects include direct spillovers from China on its trading partners, subsequent spillins among them, and spillbacks on China itself. The paper finds that the network effects most likely will be substantial, may amplify initial shock, and change the direction of its propagation. The impact on Asia and Pacific will be the strongest followed by the Middle East and Central Asia. The impact on sub-Saharan Africa would be noticeable only for some countries. Spillovers on Europe, including the Euro area, will be moderate, and spillovers on the Western Hemisphere, including the United States, would be very marginal. Metal and non-fuel commodity exporters may experience the largest negative impact.